ChemInform Abstract: Crystal Structure and Hydrogenation Properties of Pd5As. Issue 17 (April 2016) - Kohlmann, H.; Vasseur, M.; Sayede, A.; Lefevre, G.; Sander, J. M.; Doyle, S.
Abstract: Single phase Pd5 As is prepared by heating stoichiometric amounts of the elements (evacuated silica tubes, 973 K, 4 d).